The relationship of pregnant women knowledge About iron deficiency Anemia and the role of family In Compliance in consuming Fe tablets in health center - Hary Yadi; Asmarita Jasda (Alma Ata University Press, 2019)
Pregnancy leads to increased energy metabolism, hence the need for energy and other nutrients increases during pregnancy. Increased energy and nutrients are needed for growth and development of the fetus, the increase in the amount of the uterus, changes in the composition and metabolism of the mother's body. If  levels of iron in the body of pregnant women is less, then there will be a condition called anemia. That's because iron is an essential microelement for the body. This substance is especially needed in hemopoiesis (blood formation), ie in the synthesis of hemoglobin. The purpose of this study was  to determine Knowledge of Pregnant Women About Iron Deficiency Anemia and Family Role With Compliance In Consuming Iron Tablet in health center . This study was a quantitative research, analytical, with cross sectional study subjects all mothers who have antenatal and get a tablet Fe in Tanjungpinang health center  based on data consist of 40 respondents. The result of this study was significat relationship between knowledge of pregnant women to iron deficiency anemia with Compliance Consuming Tablet iron  show the value of p 0814, the p-value is greater than the p value 0:05 was shows that no have correlation between knowledge of pregnant women about iron deficiency anemia with Compliance Consuming Iron Tablets. Family Role in monitoring drinking iron tablet  with Compliance Consuming Iron Tablets shows the value of p 0.00 is smaller than the value of α 0.05. This shows that there is a relationship between family role in monitoring drinking iron tablet with compliance consuming iron tablet. This study  indicated to increase Knowledge Level Of a Person On Iron Deficiency Anemia  Not Consume The Influence Behavior Of Iron Tablet  But Can Improve The Role Of Family In Compliance With Pregnant Women Eat Iron Tablet.